2020
DOI: 10.1111/aas.13682
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and health‐related quality of life 1 year after acute brain injury: An observational study

Abstract: Background: Cognitive impairment and reduced health-related quality of life (HRQoL) are well-established sequelae of critical illness. Studies on survivors of critical illness have found delirium to be a predictor of these conditions, but evidence regarding survivors of acute brain injury is sparse. We aimed to explore if delirium duration was associated with 1-year cognitive impairment and reduced HRQoL in patients with acute brain injury. Method: Intensive care unit (ICU) delirium was assessed using the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The updated resulted in a further 839 papers, included duplicates with the first search, of which seven were included. Across the initial and updated search, fourteen of the included studies reported costs [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and eleven reported data on HRQOL [26][27][28][29][30][31][32][33][34][35][36] (Figure 1). The most frequent reasons for exclusion during the full text screening were related to papers not concerning costs or HRQoL of Delirium (wrong outcome) and no or inappropriate adjustment for confounding.…”
Section: Study Selectionmentioning
confidence: 99%
“…The updated resulted in a further 839 papers, included duplicates with the first search, of which seven were included. Across the initial and updated search, fourteen of the included studies reported costs [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and eleven reported data on HRQOL [26][27][28][29][30][31][32][33][34][35][36] (Figure 1). The most frequent reasons for exclusion during the full text screening were related to papers not concerning costs or HRQoL of Delirium (wrong outcome) and no or inappropriate adjustment for confounding.…”
Section: Study Selectionmentioning
confidence: 99%
“…Cognitive function is the mental activity or process of using thought, experience, and feeling to obtain knowledge and understanding, including attention, working memory, language, spatial orientation, and execution ( Van de Geer and Jaspars, 1966 ; Larsen et al, 2020 ; Liu et al, 2020 ). It plays an important role in the performance of young adults who are in the critical period of growth and development ( Sharma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%